Diverse hematological phenotypes of β‐thalassemia carriers. Issue 1 (28th April 2016) - Luo, Hong‐Yuan; Chui, David H.K.
Abstract : Most β‐thalassemia carriers have mild anemia, low mean corpuscular volume and mean corpuscular hemoglobin, and elevated hemoglobin α2 (HbA2 ). However, there is considerable variability resulting from coinheritance with α‐ and/or δ‐globin gene mutations, dominant inheritance of β‐thalassemia mutations, highly unstable variant globin chains, large deletions removing part or all of the β‐globin gene cluster, loss of heterozygosity of the β‐globin gene cluster during development, or concomitant erythroid enzyme or membrane protein abnormalities. Recognition of the specific abnormality and correct diagnosis can allay anxiety and unnecessary investigation, help formulate treatment programs, and deliver appropriate genetic and family counseling.